2019
DOI: 10.1007/s40544-019-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on tribological behaviors of MoS2 and WS2 quantum dots as lubricant additives in ionic liquids under severe conditions

Abstract: Despite excellent tribological behaviors of ionic liquids (ILs) as lubricating oils, their friction-reducing and anti-wear properties must be improved when they are used under severe conditions. There are only a few reports exploring additives for ILs. Here, MoS 2 and WS 2 quantum dots (QDs, with particle size less than 10 nm) are prepared via a facile green technique, and they are dispersed in 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm]PF 6 ), forming homogeneous dispersions exhibiting long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore, several studies revealed ecofriendly ILs additives had demonstrated excellent nanodispersions, especially in lube oils. [67][68][69][70] ILs are used as a medium to synthesis nanoparticles in the base oil. Nanoparticles are mainly utilized in ILs to observe the reaction in intermolecular structure, which changes the van der Waals, electrostatic, and hydrogen bonding in the base oil.…”
Section: Effect Of Ils On the Dispersion Stabilitymentioning
confidence: 99%
“…Furthermore, several studies revealed ecofriendly ILs additives had demonstrated excellent nanodispersions, especially in lube oils. [67][68][69][70] ILs are used as a medium to synthesis nanoparticles in the base oil. Nanoparticles are mainly utilized in ILs to observe the reaction in intermolecular structure, which changes the van der Waals, electrostatic, and hydrogen bonding in the base oil.…”
Section: Effect Of Ils On the Dispersion Stabilitymentioning
confidence: 99%
“…These impressive physical properties have motivated scholars to examine the applicability of WS 2 and MoS 2 QD additives [96]. Gong et al [97] prepared MoS 2 and WS 2 QDs and dispersed them in 1-butyl-3-methylimidazolium hexafluorophosphate to obtain homogeneous dispersions with long-term stability. According to the tribological results, adding WS 2 and MoS 2 QDs to this IL significantly enhanced the friction-reduction and antiwear performance of the base fluid.…”
Section: Metal Sulfidesmentioning
confidence: 99%
“…Several classes of two-dimensional (2D) nanomaterials, such as molybdenum disulfide (MoS 2 ), graphene nanoplatelets (GNPs), and hexagonal boron nitride (BN), have been studied as lubricant additives due to their unique lamellar structure. The weak van der Waals interlayer bonding allows the basal planes to easily slip away, thus greatly reducing the friction coefficient. However, they still possess some drawbacks.…”
Section: Introductionmentioning
confidence: 99%